In vitro Plant Regeneration in Mungbean (Vigna radiate (L.) Wilczek) (Plant Tissue Culture and Biotechnology, 2009)
An efficient regeneration protocol without the intervention of callus using cotyledon explants of three mungbean varieties namely, BARI mug-3, BARI mug-5 and BINA mug-5 was developed. Best response toward multiple shoot regeneration in BARI mug-5 and BINA mug-5 was observed on MS supplemented with 0.5 and 0.5 mg/l Kn. However, for BARI mug-3, MS supplemented with 0.5 mg/l BAP and 0.1 mg/l Kn was found to be most effective for multiple shoot regeneration. Half-strength of MS supplemented with 0.5 mg/l IBA was found to induce healthy roots from the excised shoots in all the three mungbean varieties. In vitro regenerated plantlets with well developed roots were successfully established in soil.  Key words: Regeneration protocol, mungbean, Vigna radiata D.O.I. 10.3329/ptcb.v17i2.3241 Plant Tissue Cult. & Biotech. 17(2): 209-216, 2007 (December)